An 8-year-old boy with severe disseminated Staphylococcus aureus infection - Wangjirapan A. (2017)
We report an 8-year-old boy who developed high fever and low-back pain. He was diagnosed as having a paravertebral abscess with severe disseminated Staphylococcus aureus infection. He received intravenous antibiotics and drainage of the abscess. Afterwards, he developed thrombosis, endocarditis and empyema thoracis. He received further intravenous antibiotics and proper drainages for his conditions. He eventually recovered well. This case highlights the need for rapid diagnosis and appropriate treatment of severe S aureus infection to prevent serious complications. Copyright © 2012 BMJ Publishing Group.